2020
DOI: 10.3390/biom10050703
|View full text |Cite
|
Sign up to set email alerts
|

Soluble Epoxide Hydrolase Inhibition to Face Neuroinflammation in Parkinson’s Disease: A New Therapeutic Strategy

Abstract: Neuroinflammation is a crucial process associated with the pathogenesis of neurodegenerative diseases, including Parkinson’s disease (PD). Several pieces of evidence suggest an active role of lipid mediators, especially epoxy-fatty acids (EpFAs), in the genesis and control of neuroinflammation; 14,15-epoxyeicosatrienoic acid (14,15-EET) is one of the most commonly studied EpFAs, with anti-inflammatory properties. Soluble epoxide hydrolase (sEH) is implicated in the hydrolysis of 14,15-EET to its corresponding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 168 publications
(225 reference statements)
0
21
0
Order By: Relevance
“…In 1981, Capdevila et al (1981) firstly reported that AA could be metabolized to EETs by CYP in the liver. Since then, plenty of studies have demonstrated that EETs played important roles in several diseases, such as kidney diseases ( Hye Khan et al, 2016 ; Deng et al, 2017 ; Wang et al, 2019 ), neurodegenerative diseases ( Atone et al, 2020 ; Pallas et al, 2020 ), rheumatic arthritis ( Hoxha, 2018 ; Hoxha and Zappacosta, 2020 ), and especially CVD ( Xu et al, 2011 ; Chen and Wang, 2013 ).…”
Section: Eets and Its Effects In Cvdmentioning
confidence: 99%
“…In 1981, Capdevila et al (1981) firstly reported that AA could be metabolized to EETs by CYP in the liver. Since then, plenty of studies have demonstrated that EETs played important roles in several diseases, such as kidney diseases ( Hye Khan et al, 2016 ; Deng et al, 2017 ; Wang et al, 2019 ), neurodegenerative diseases ( Atone et al, 2020 ; Pallas et al, 2020 ), rheumatic arthritis ( Hoxha, 2018 ; Hoxha and Zappacosta, 2020 ), and especially CVD ( Xu et al, 2011 ; Chen and Wang, 2013 ).…”
Section: Eets and Its Effects In Cvdmentioning
confidence: 99%
“…There are multiple lines of evidence suggesting that soluble epoxide hydrolase (sEH) deficiency or inhibition can attenuate parkinsonism in MPTP-treated mice (Qin et al, 2015;Pallas et al, 2020). For example, deficiency and inhibition of sEH attenuates the loss of TH-positive cells and improves rotarod performance (Qin et al, 2015).…”
Section: Soluble Epoxide Hydrolase Inhibitionmentioning
confidence: 99%
“…Thus, sEH inhibition might be a powerful tool to protect dopaminergic neurons in PD (Qin et al, 2015). In addition to having anti-inflammatory properties, EETs may have numerous benefits such as antioxidant effects, a reduction in mitochondrial dysfunction and apoptosis and improved cerebral blood flow (Pallas et al, 2020).…”
Section: Soluble Epoxide Hydrolase Inhibitionmentioning
confidence: 99%
“…The neuroinflammation can be controlled by either suppressing the expression and release of pro-inflammatory mediators such as iNOS, Iba1, TNF-a, or increasing anti-inflammatory cytokines, including IL-10 by polarized microglia, which is greatly affected by endogenous Ep-PUFAs, in particular EETs [ 136 , 138 , 139 ]. Several studies have shown that deletion or inhibition of sEH induces production of anti-inflammatory cytokines such as IL-10, while reducing pro-inflammatory mediators including IFN-γ, and decreasing TNF-α localization and circulation [ 176 , 211 , 212 ].…”
Section: Ep-pufas and Neuroinflammationmentioning
confidence: 99%